Coupling ICESat-2 and Sentinel-2 data for inversion of mangrove tidal flat to predict future distribution pattern of mangroves - Xiaoyong Ming; Yichao Tian; Qiang Zhang; Yali Zhang; Jin Tao; Junliang Lin (International Journal of Applied Earth Observations and Geoinformation)
Tidal flats represent one of the Earth’s most critical ecosystems characterized by substantial ecological value, but these areas are also among the most fragile ecosystems. A detailed topography survey of tidal flat is essential for exploring how tidal flat ecosystems respond to environmental changes and for predicting morphological shifts, thereby impacting the protection and restoration of mangrove ecosystems. However, there is still a dearth of data available for mangrove tidal flat topography, as the majority of measurements primarily rely on traditional cartographic methods or small-scale surveys. Therefore, we aim to rely entirely on Earth observation satellite platforms, combining satellite-based Light Detection and Ranging (LiDAR) and optical remote sensing to monitor extensive mangrove tidal flat topography. This methodology was rigorously applied and validated on China’s largest and most representative mangrove tidal flats, revealing a Root Mean Square Error (RMSE) not exceeding 7.5 cm and an R-squared value surpassing 0.89 when compared to airborne LiDAR data. We use the inundation frequency derived from the long-term Sentinel-2 image sequences and elevation data extracted from the Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) to establish a specific relationship between inundation frequency and ground elevation using both classical and generalized regression models, a mangrove tidal flat topography covering 76.9 km2 was generated. Our findings delineate suitable distribution areas for mangroves in the Maowei Sea, covering an expansive 18.2 km2.